Efektivitas Fitoremediasi Tumbuhan Air Terhadap Penurunan Kadar Amonia pada Air Budidaya Ikan Lele (Clarias Sp.) - Rubiyah; Melfa Aisyah Hutasuhut; Khairunnisa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effectiveness of aquatic plant phytoremediation in reducing ammonia levels in catfish (Clarias sp.) cultivation water. This study used a non-factorial Randomized Block Design (RBD) with 5 treatments and 3 replications (n = 15 experimental units), consisting of a control without aquatic plants (P0) and four aquatic plant species, namely water lettuce (Pistia stratiotes L.) (P1), water hyacinth (Eichhornia crassipes L.) (P2), duckweed (Lemna sp.) (P3), and water spinach (Ipomoea aquatica L.) (P4), each placed at 25% of the circumference of a 14-liter container for 28 days of observation. quality parameters including ammonia, DO, BOD, and COD were measured using a UV-Visible spectrophotometer at the laboratory and pH was measured using a pH meter in the field on days 0, 14, and 28. Data were analyzed using One Way ANOVA and Duncan's Multiple Range Test (DMRT) post-hoc test at a significance level of ≤ 5%. The results showed that all aquatic plant species effectively reduced ammonia levels, where Eichhornia crassipes (water hyacinth) produced the highest reduction of up to 79% and a 10% decrease in pH levels compared to the untreated control, while Lemna sp. (duckweed) reduced DO levels by up to 25%, BOD levels by 1.21%, and COD levels by 1.28% in the catfish cultivation water. This study concludes that phytoremediation using aquatic plants, particularly water hyacinth, is proven to be the most effective natural alternative for reducing ammonia levels in catfish cultivation water and has potential for application in sustainable aquaculture systems. Keywords: Ammonia, Phytoremediation, Aquatic Plants